Trayectorias artísticas-militantes: memoria y fotografía en el Museo de Arte y Memoria, de La Plata (Argentina) (2015)
This work presents and reflects on the construction of an “art (photo) - Militant memory” field in Argentina. Inspired by the bourdiana theory, work around four artists paths that converge in the art space art Museo de Arte y Memoria de La Plata. With that, we understand the different relations of alliance and solidarity between these actors and institutions in shaping a specific type of art relevant to works by the memory of Argentina’s military dictatorship.